De Novo Genome Assembly for an Endangered Lemur Using Portable Nanopore Sequencing in Rural Madagascar - Lindsey Hauff; Noa Elosmie Rasoanaivo; Andriamahery Razafindrakoto; Hajanirina Ravelonjanahary; Patricia C. Wright; Rindra Rakotoarivony; Christina M. Bergey (Ecology and Evolution)
ABSTRACT As one of the most threatened mammalian taxa, lemurs of Madagascar are facing unprecedented anthropogenic pressures. To address conservation imperatives such as this, researchers have increasingly relied on conservation genomics to identify populations of particular concern. However, many of these genomic approaches necessitate high‐quality genomes. While the advent of next‐generation sequencing technologies and the resulting reduction in associated costs have led to the proliferation of genomic data and high‐quality reference genomes, global discrepancies in genomic sequencing capabilities often result in biological samples from biodiverse host countries being exported to facilities in the Global North, creating inequalities in access and training within genomic research. Here, we present the first published reference genome for the endangered red‐fronted brown lemur (Eulemur rufifrons) from sequencing efforts conducted entirely within the host country using portable Oxford Nanopore sequencing. Using an archived E. rufifrons specimen, we conducted long‐read, nanopore sequencing at the Centre ValBio Research Station near Ranomafana National Park, in rural Madagascar, generating over 750 Gb of sequencing data from 10 MinION flow cells. Exclusively using this long‐read data, we assembled 2.157 gigabase, 2980‐contig nuclear assembly with an N50 of 101.6 Mb and a 17,108 bp mitogenome. The nuclear assembly had 30× average coverage and was comparable in completeness to other primate reference genomes, with a 96.1% BUSCO completeness score for primate‐specific genes. As the first published reference genome for E. rufifrons and the only annotated genome available for the speciose Eulemur genus, this resource will prove vital for conservation genomic studies while our efforts exhibit the potential of this protocol to address research inequalities and build genomic capacity.